(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
When investigating deaths due to cut-throat injury, the forensic pathologist is often in a dilemma with regard to the manner of death. Though differentiating features are elaborated in various medical literatures, one always comes across unusual cases which do not fit into the classical criteria. Presence of tentative cuts, defence injuries and other associated injuries are commonly looked into apart for analysing the pattern of cut-throat injury alone with respect to its multiplicity, direction and involvement of deeper structures. The case further gets complex when the crime scene is altered and staged to simulate and mislead the investigators. Here, we present a case where according to the history a 23-year-old female had locked herself up in the bedroom of her house and had cut her throat with a knife. Though the case was brought initially as suicide, later after the autopsy and crime scene visit, it turned out to be a case of homicide. The perpetrator had staged the crime scene to make the case look like suicide.